Mobile Phone and Infertility: Analysis of different Parameters of Semen in Infertile Males Using Phones versus Non. Mobile Phone User - Anwar All Jamali, Tabinda Taqi, Hajra Naila Rahu, Ghulam Mustafa Jamali, Ashok Kumar Lohano, Bhojo Mal Tanwani (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: To investigate the effects of mobile phone use on semen parameters, particularly quantity, motility and morphology of sperms in subjects using mobile phones and controls not using mobile phones with infertility. Methods: This was a cross-sectional research. performed in the department of Medicine PUMHS, Nawabshah, during January 2015 to December 2017. A total of 385 male subjects of young age group, age ranging from 20-40 years were included. The subjects were categorized as mobile phone users and non-users. After taking consent, a structured proforma was filled by the researcher, including demographic and clinical information and two questions related to research. All the data collected was statistically analyzed. Results: There were total 385 males included in study. DitThrent groups were assessed for semen analysis. Abnormal Semen parameters regarding sperm count and motility were more common in infertile males using mobile phones in comparison to non mobile phone users. Conclusion: A relationship occurs among mobile phone usage, sperm count and decreased sperm motility.